2019
DOI: 10.2478/acs-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge as a source of triclosan-resistant bacteria

Abstract: Subinhibitory concentrations of antibiotics and biocides in wastewaters and sewage sludge have a great impact on the development of antibiotic resistance and its spread among bacteria. The aim of this work was to determine the occurrence of coliform bacteria and enterococci resistant to biocide triclosan in samples of sewage sludge. Subsequently, isolated strains of coliform bacteria were identified and characterized in terms of their antibiotic susceptibility and ability to form a biofilm. Occurrence of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Although humans are exposed to low doses of many chemicals, their presence in surface, ground and drinking water indicates their persistence and potential accumulation in the human body at high doses [6,55,56]. TCS, previously a commonly used antimicrobial compound, has raised public concerns due to evidence that suggests its link to alteration of host physiology [51], disruption of microbial communities [9,57] and an increase in bacterial resistance [7,[58][59][60]. Moreover, TCS is also linked to induce risk among neonates via breastmilk intake [5,56,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although humans are exposed to low doses of many chemicals, their presence in surface, ground and drinking water indicates their persistence and potential accumulation in the human body at high doses [6,55,56]. TCS, previously a commonly used antimicrobial compound, has raised public concerns due to evidence that suggests its link to alteration of host physiology [51], disruption of microbial communities [9,57] and an increase in bacterial resistance [7,[58][59][60]. Moreover, TCS is also linked to induce risk among neonates via breastmilk intake [5,56,61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that human skin and oral mucosa are capable of absorbing TCS, which results in the detection of TCS in various tissues and body fluids [4,5]. Consumer and commercial product wastes are known to contaminate the environment and water sources and the presence of TCS in these materials could have an adverse impact on health [6,7]. Continuous exposure to TCS through various consumer products, as well as the deposition of TCS in river water and soil, leads to the emergence of antimicrobial-resistant bacteria [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to biotransformation made triclosan unsuitable for biological treatment. Lépesová & Krahulcová (2019), identified bacterial strain such as Citrobacter freundii and Serratia spp. known for its triclosan resistance in sewage sludge rendering resistance to biotransformation (Lépesová & Krahulcová 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lépesová & Krahulcová (2019), identified bacterial strain such as Citrobacter freundii and Serratia spp. known for its triclosan resistance in sewage sludge rendering resistance to biotransformation (Lépesová & Krahulcová 2019). Adsorption is known to remove triclosan effectively with its limitations in the maintenance and regeneration of adsorbent.…”
Section: Introductionmentioning
confidence: 99%